The Foundation is Gone - Hwozdek, Jenny (Homœopathic Links, 2013)
This case explores how a clientʼs Lyme-like symptoms become a somaticized expression of her grief over losing her father. The Mineral Kingdom struggle of establishing a basic identity, which unfolds in this woman, has a breadth and depth of expression that fails to be adequately captured by the usual suspects populating Row Two of the Periodic Table – the row most suited to assist in the process of being “born” as an individuated being into the world. The nearly quantum expansion of Row Two remedies that has become available via the Carbon Compounds allows us, as homeopaths, to foster our clientʼs evolutionary process with ever increasing nuance and precision.
Keywords: Carbons; Salicylic acid; Lyme disease; Borreliosis